Determination of Enteric Methane Emission from Grazing Brahman Steers in the Tropical Dry Forest Ecosystem of Costa Rica - Montenegro, Johnny (2018)
This research was conducted to determine the actual enteric methane emission of Brahman steers grazing different unfertilized grass species in the tropical dry forest ecosystem: naturalized, Brachiaria brizantha cv. Marandu, and B. decumbens cv. Basilik. In each grass, availability of dry matter, digestibility, crude protein, and fiber content were determined; and for methane emission, the sulfur hexafluoride (SF6) technique was used to measure it. The daily methane emission per animal was similar (P>0.05) among grass species (168.0±6.2, 178.8±6.2 and 166.4±6.2 g, for natural, B. brizantha and B. decumbens respectively). According to estimated consumption levels, differences were detected in the amount of methane emitted per unit of dry matter intake (DMI), being higher (P<0.01) in natural grass (21.8±0.7 g CH4 kg-1 DMI) compared to that in B. brizantha (19.6±0.8 g CH4 kg-1 DMI); intermediate level was determined with B. decumbens (20.3±0.8 g CH4 kg-1 DMI). The consumed energy emitted as methane and expresses as Ym had a range from 6.0 to 6.6; and it was clear that as consumption increased, the energy utilization efficiency improved and, therefore, decreased the conversion factor.